Time course of hemolysis in respiratory alkalosis - A. Babaknia; M.A. Khoyi (Acta Medica Iranica, 1969)
Blood pH and plasma hemoglobin concentration were measured in dog undergoing hyperventilation with or without 6 %CO 2. Blood pH rose in the first minutes in the alkalotic group and hemolysis appeared mostly during second hour after alkalosis was established. It increased gradually during the following hours of hyperventilation. No hemolysis was observed in the group undergoing hyperventilation with 6% C02. It is concluded thal hemolysis is unrelated to mechanical action of hyperventilatroi n and in due to alkalosis. the possible cause of hemo lysis and related Iitrature is discussed.